The role of economic conditions on humor generation and attitude towards humorous TV commercials - Hatzithomas, Leonidas; Boutsouki, Christina; Zotos, Yorgos (My University, 2016)
A two-phase experimental study investigates the role of economic conditions on humor generation and on the relationship between perceived humor and attitude toward the ad (Aad). It designates that the economic context affects the generation of humor and the relationship between perceived humor and Aad; TV commercials can more effectively create humor as well as positive Aad in an expansion rather than in a recession. The generation of humor during a recession, requires a combination of high levels of perceived surprise and low levels of perceived irritation. In the same vein, attitude towards a humorous ad, in a recession, increases significantly only when there is high perceived humor and low perceived irritation. Specific managerial and theoretical implications are discussed.
Keywords: Economic conditions; Greece; Humorous advertising; Irritation; Surprise